Determining prognostic factors in the treatment of primary hemifacial spasm: Clinical outcomes and complications. A literature review - Juan Carlos Acevedo-González; Alex Taub-Krivoy; Julian Alfonso Sierra-Peña; Julian Geronimo Lizarazo (World Neurosurgery: X)
Objective: Primary Hemifacial Spasm (PHFS) significantly impacts quality of life, necessitating effective treatment like microvascular decompression of the facial nerve. This study aims to identify prognostic factors related to surgical treatment to enhance outcomes and minimize complications. A systematic review of literature from the past five years was conducted. Methods: Following PRISMA guidelines, we systematically searched databases like PubMed, Embase, Scopus, Ovid, EBSCO, and Cochrane using keywords such as 'Hemifacial spasm,' 'Microvascular decompression,' 'Neurovascular conflict,' and 'Surgical techniques.' The search spanned January 2018 to November 2023. The 'Rayyan' program facilitated data compilation. Each author reviewed abstracts, applying inclusion criteria like systematic reviews, clinical trials, observational studies, and case series, while excluding theoretical or non-English articles. Results: Of 26 selected articles, those solely addressing PHFS treatment with botulinum toxin and lacking surgical procedure data were excluded. Thus, our analysis focused on 16 articles, including meta-analyses, systematic reviews, clinical trials, and observational studies. Discussion: Microvascular decompression at the cerebellar pontine angle is the mainstay treatment for hemifacial spasm. Despite limited statistically significant prognostic factors in the literature, overarching recommendations aim to improve outcomes, minimize complications, and prevent recurrences. Key considerations include surgeon expertise, precise techniques, thorough nerve exploration, identifying the conflict's cause, and intraoperative monitoring. Conclusions: PHFS significantly impacts patients' lives, necessitating timely surgical intervention if initial treatments fail. While statistically significant prognostic factors may be lacking, this study highlights crucial considerations for successful treatment.